1994
DOI: 10.1029/93jc02777
|View full text |Cite
|
Sign up to set email alerts
|

Sun glitter radiance and radar cross‐section modulations of the sea bed

Abstract: Aircraft and satellite‐borne multispectral sensors such as ocean color scanners, spectrometers, and scanning Lidar's have proved to be effective in detecting submarine shallow‐water bottom topography in clear coastal waters. For such studies the blue‐green band of the visible electromagnetic spectrum (wavelength between 400 and 580 nm) is used, because natural light in this range has the deepest penetration into the water column. However, if the water becomes turbid, the reflection from the submarine sea bed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…Variations in the sea surface roughness due to submarine topography can result in modulation of the radiance intensity in optical imageries and, as a result, submarine topographic features are frequently observed in optical satellite imageries since the launch of SKYLAB [Hennings et al, 1988[Hennings et al, , 1994Gagliardini and Colón, 2004;Matthews et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variations in the sea surface roughness due to submarine topography can result in modulation of the radiance intensity in optical imageries and, as a result, submarine topographic features are frequently observed in optical satellite imageries since the launch of SKYLAB [Hennings et al, 1988[Hennings et al, , 1994Gagliardini and Colón, 2004;Matthews et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…[5] The relaxation rate (or wave growth rate) m r is one of the most important parameters in imaging models of sea bottom topography for both space-borne radar [Alpers and Hennings, 1984;Zimmerman, 1985;Vogelzang et al, 1997] and Sun glitter [Hennings et al, 1994]. The magnitude of water depth variations retrieved from SAR or Sun glitter imagery depends critically on making a correct choice for m r .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the sun glitter geometry model, it has been found that the signature of sun glitter images depends strongly on the viewing angle. 19,23,24 He et al 25 discussed the brightness reversal of the Taiwan Banks submarine sand waves in sun glitter images from charge-coupled diodes onboard the HJ-1B satellite. Therefore, multiangle sun glitter images can present useful additional information compared with single angle images.…”
Section: Introductionmentioning
confidence: 99%
“…The Cox-Munk model established a fundamental theory enabling sun glitter images to detect marine dynamic processes, and sun glitter remote sensing has played an important role in a wide range of oceanographic studies, including internal wave detection, 15,16 oil slick detection, 17 and shallow underwater topography mapping. 7,18 Hennings et al 19 developed a key theory of the sun glitter imaging mechanisms for underwater bottom topography based on the Cox-Munk model and SAR imaging mechanisms. He et al, 20 Shao et al, 21 and Zhang et al 22 used sun glitter imagery to observe sand waves in the Taiwan Banks, and statistically analyzed their distributions and characteristics.…”
Section: Introductionmentioning
confidence: 99%